Rabbinic drinking: what beverages teach us about rabbinic literature - Rosenblum, Jordan (University of California Press, 2020)
Cover -- Rabbinic Drinking -- Title -- Copyright -- Dedication -- CONTENTS -- Acknowledgments -- Introduction -- 1. The Literature and History of the Rabbinic Movement -- 2. Biblical Interpretation -- 3. Social Boundaries -- 4. Gender and Sexuality -- 5. Magic, Idolatry, and Illicit Religious Practice -- 6. Sabbath, Festivals, and Holidays -- 7. Prayer and Ritual -- 8. Ritual Purity -- 9. Health and Hygiene -- Conclusion -- Glossary -- Subject Index -- Citation Index.